2023
DOI: 10.5644/ama2006-124.394
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical Variations of Vascular Anatomy in Meckel’s Diverticulum

Abstract: <p><strong>Objective</strong>. The objective of the current study was to describe the anatomical variations of vessels observed in patients with Meckel’s Diverticulum.</p><p><strong>Methods</strong>. A narrative review of the literature was undertaken by means of the PubMed database, using the terms: “Meckel’s Diverticulum AND vessels”, “Meckel’s Diverticulum AND anatomical variation” and “Meckel’s Diverticulum variation”. Classical anatomical textbooks were also used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
(67 reference statements)
0
1
0
Order By: Relevance
“…It is easily confused with acute abdomen such as acute appendicitis in children, which is difficult to recognize on imaging. Recent studies have shown that Meckel's diverticulum is difficult to diagnose[ 6 ]. A case of Meckel's diverticulum combined with appendicitis in an adult was recently reported[ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is easily confused with acute abdomen such as acute appendicitis in children, which is difficult to recognize on imaging. Recent studies have shown that Meckel's diverticulum is difficult to diagnose[ 6 ]. A case of Meckel's diverticulum combined with appendicitis in an adult was recently reported[ 7 ].…”
Section: Introductionmentioning
confidence: 99%